Analysis of Cash Flow Shenanigans on PT. Pertamina (Persero) Tbk - Natalis Christian; Fiona Vinelia; Juwenni Juwenni; Michael Learns Tay; Meliesa Chandrawati (Lafadz Jaya Publisher, 2023)
Currently, In Indonesia, there are a rising number of instances of financial figures being fraudulently altered. An alleged corruption case occurred from 2009 to 2012. Where, PT Pertamina Patra Niaga entered into a non-cash fuel sale and purchase agreement with PT Asmin Koalindo Tuhup. This study aims to analyze the alleged corruption case that happened to PT Pertamina and analyze fraud cases using cash flow shenanigans. Secondary data for this study was obtained from PT Pertamina (Persero) Tbk's official website. The financial statements of the company for the years prior to, during, and following the fraud will be compared in this study to draw conclusions. The majority of the ratio proves that PT Pertamina experienced a decline in business in 2009. Where as PT. Pertamina needs more time to sell their inventoryand collect their receivable.